2015
DOI: 10.1007/s11255-015-0937-9
|View full text |Cite
|
Sign up to set email alerts
|

Should we use statins in all patients with chronic kidney disease without dialysis therapy? The current state of knowledge

Abstract: Meta-analyses results suggest that statins are associated with lipid lowering, cardiovascular and anti-proteinuric benefits in CKD patients. However, their effects on overall and cardiovascular mortality are much less obvious. Bearing in mind the advantageous effects and low risk of adverse effects, it seems that mild renal impairment should not exclude these patients from receiving a statin. However, because CKD patients in stages III-V are underrepresented in clinical trials, administration of statins to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 84 publications
0
14
0
3
Order By: Relevance
“…Applying guideline based LDL cholesterol targets may be less useful in the CKD population. Despite this, convincing cardiovascular event risk reduction benefits of statins have been demonstrated in the non-dialysis-dependent CKD population though the benefits are dampened compared to the general population and appear more uncertain with more advanced stages of CKD (45, 46). In a data analysis of the Modification of Diet in Renal Disease (MDRD) Study, a multicenter randomized clinical trial with mainly stage 3 and 4 CKD patients, hyperlipidemia was found not to be independently associated with all-cause mortality, CVD mortality or CKD progression (47).…”
Section: The Lipid Profile In Ckd and Its Relationship With Cvdmentioning
confidence: 99%
“…Applying guideline based LDL cholesterol targets may be less useful in the CKD population. Despite this, convincing cardiovascular event risk reduction benefits of statins have been demonstrated in the non-dialysis-dependent CKD population though the benefits are dampened compared to the general population and appear more uncertain with more advanced stages of CKD (45, 46). In a data analysis of the Modification of Diet in Renal Disease (MDRD) Study, a multicenter randomized clinical trial with mainly stage 3 and 4 CKD patients, hyperlipidemia was found not to be independently associated with all-cause mortality, CVD mortality or CKD progression (47).…”
Section: The Lipid Profile In Ckd and Its Relationship With Cvdmentioning
confidence: 99%
“…Statins not only lower lipid profiles, they also exert anti-proteinuric effects [13]. However, the beneficial effects of statins had not previously been assessed according stage of CKD, dosage, and treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, statin therapy improved renal function and reduced proteinuria [1315], possibly due to their anti-inflammatory activity and improvement of endothelial function, which reduces abnormal permeability to plasma proteins [6, 1620]. Thus, statin administration may benefit CKD patients due to its enhancement of renal perfusion by improving endothelial and cardiac function [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The greatest benefits are noted in patients with coexisting CKD and diabetes [131]. There is no clear evidence to conclude beyond doubt that statin or statin/ezetimibe therapy is beneficial in adults with stage 5 CKD undergoing dialysis treatment.…”
Section: Treatment Of Lipid Disorders In Selected Populationsmentioning
confidence: 99%
“…There is no clear evidence to conclude beyond doubt that statin or statin/ezetimibe therapy is beneficial in adults with stage 5 CKD undergoing dialysis treatment. Cardiovascular mortality in this patient group is mainly associated with heart failure and cardiac dysrhythmia [131, 132]. However, treatment continuation is indicated in those patients who were treated for dyslipidaemia at the time of starting dialysis therapy.…”
Section: Treatment Of Lipid Disorders In Selected Populationsmentioning
confidence: 99%